2021
DOI: 10.1186/s12955-021-01895-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between health literacy and health-related quality of life among school-aged children in regional China

Abstract: Objectives To examine the association between health literacy (HL) and health-related quality of life (HRQoL) among primary and high school students in Nanjing, China. Methods A cross-sectional study was conducted among randomly selected primary (graders 4–6), junior (graders 7–9) and senior (graders 10–12) high school students in 2018 in Nanjing Municipality of China. HRQoL, the outcome variable, was assessed with the validated Chinese version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In 89 relevant papers in HL, studies authored by Chinese scientists are the most prevalent, with 27 studies that surveyed HL levels in various groups of people. They were patients 22 -27 or general public, secondary, 28 -30 high school, 30,31 college students, 32,33 women, 34 12 years old and above, 16,15,35 -43 or older adults. 44 -47 Taiwan had the second-highest number of HL measurement articles, with 16 published papers.…”
Section: Resultsmentioning
confidence: 99%
“…In 89 relevant papers in HL, studies authored by Chinese scientists are the most prevalent, with 27 studies that surveyed HL levels in various groups of people. They were patients 22 -27 or general public, secondary, 28 -30 high school, 30,31 college students, 32,33 women, 34 12 years old and above, 16,15,35 -43 or older adults. 44 -47 Taiwan had the second-highest number of HL measurement articles, with 16 published papers.…”
Section: Resultsmentioning
confidence: 99%
“…The results of a study in 2022 showed that there is a significant relationship between the level of health literacy and the dimensions of quality of life (physical dimension, psychological dimension, and overall quality of life), so that people with higher health literacy have higher physical and mental quality of life as well as higher health‐related quality of life 36 . It has been shown in a study that people with sufficient health literacy had a higher quality of life, and there is a relationship between health literacy and the physical and mental aspects of quality of life 37 …”
Section: Discussionmentioning
confidence: 99%
“…36 It has been shown in a study that people with sufficient health literacy had a higher quality of life, and there is a relationship between health literacy and the physical and mental aspects of quality of life. 37 It was shown in a systematic review that health literacy was related to quality of life, and health knowledge, health behavior, health beliefs, and health skills were related to quality of life. There is, however, a need for more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a comprehensive review, it was shown that the individuals with lower HL had poorer global health status, were more likely to express symptoms of depression, and had higher all-cause mortality rates [ 8 ]. In addition, a study on Indonesian adolescents identified that HL was related to health behaviors, including physical activity [ 12 ], while another study recorded that HL was associated with health-related quality of life (i.e., self-perception of mental and physical health conditions) among Chinese schoolchildren [ 13 ]. Moreover, low levels of HL were linked to increased body weight and obesity [ 14 , 15 ] and poor nutritional habits, including increased sugar, fat, and salt intake in children and adolescents [ 16 ].…”
Section: Introductionmentioning
confidence: 99%